Microcrystal cast stone as well as preparation method and application thereof
By using Fe and Ti elements in vanadium titanium magnet tailings as nucleation agents in microcrystal cast stone production and reasonably matching them with other solid waste raw materials, the problem of insufficient utilization of characteristic elements in iron tailings is solved, and high Performance of microcrystal cast stone preparation and efficient utilization of resources.
Patent Information
- Application Number
- CN202411327054.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-03
AI Technical Summary
In the prior art, Fe and Ti are used in solid waste such as iron tailings, which leads to low resource utilization efficiency.
Using vanadium titanium magnet tailings as the main raw material, using Fe, Ti and other elements as nucleation agents, and by reasonably combining other solid waste raw materials, low-added or zero-added nucleation agents are achieved, and microcrystal cast stones are prepared to reduce the preparation of Cost and increase solid waste mix.
The preparation of high-performance microcrystal cast stone has excellent mechanical properties, wear resistance and acid and alkali resistance. The solid waste rate of the product can reach more than 90%, reducing process costs.
Smart Images

Figure CN119241078A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of microcrystalline cast stone preparation, and in particular, relates to a microcrystalline cast stone and a preparation method and application thereof. Background Art
[0002] Iron tailings are waste products generated after iron ore beneficiation. Their large accumulation not only occupies land resources, but also may cause environmental pollution and safety hazards. Therefore, the resource utilization of iron tailings has become a research focus. Microcrystalline cast stone is a high-performance building material with good wear resistance, corrosion resistance and high mechanical strength. It is suitable for building decoration, chemical industry, metallurgy and other fields. In the background technology of preparing microcrystalline cast stone from iron tailings, researchers explored the use of silicate minerals in iron tailings as raw materials, and through melting, crystallization and other process steps, prepared microcrystalline cast stone with specific physical and chemical properties. These studies not only help to reduce the environmental impact of tailings, but also increase the economic value of tailings and achieve efficient utilization of resources.
[0003] The key to preparing microcrystalline cast stone from solid waste such as iron tailings lies in the regulation of ingredients and the determination of the heat treatment system. The Chinese patent with announcement number CN103073186B provides a preparation method for producing rolled microcrystalline cast stone plates from iron tailings, using iron tailings as the main raw material, and the steps are to mix the ingredients evenly, add them to a high-temperature melting furnace for melting, clarify and cool them, and then roll them into plates. After entering the crystallization kiln, they go through three stages of firing, annealing and cooling in sequence, then they are taken out of the kiln, and then trimmed, cut into sections, and put into storage; the mass percentages of the ingredients are: iron tailings 59%-70%, potassium feldspar 10%-20%, calcite 10%-20%, alumina 4%-8%, glass clarifier 10%-20%, and aluminum oxide 4%-8%. The content of the sintering agent is 0%-0.5% and the content of the industrial soda ash is 0.1%-3%; the sintering stage is a temperature from 500-600℃ to 700-750℃, and the sintering time is 60-80min; the annealing stage is a temperature from 700-750℃ to 300-400℃, and the annealing time is 50-70min; the cooling is completed in two steps, the first step is a temperature from 300-400℃ to 150-100℃, and the time is 50-70min; the second step is a temperature from 150-100℃ to 50-30℃, and the time is 20-40min. The composition of the iron tailings is further disclosed in the examples: SiO2: 67%, Al2O3: 3.32%, CaO: 4.93%, MgO: 4.03%, Fe2O3+FeO: 10%, NaO: 0.2%, K2O: 0.3%, TiO2: 0.13%; the chemical composition of the finally obtained microcrystalline cast stone plate is: SiO2: 60%, Al2O3: 12%, CaO: 15%, MgO: 3%, Fe2O3+FeO: 7%, NaO: 1%, K2O: 2%.
[0004] Among the above existing technologies, the technology of preparing microcrystalline cast stone using tailings mainly focuses on utilizing high-content components such as silicon and calcium in solid waste raw materials such as tailings. There is less application of endowment characteristic elements in solid waste such as iron tailings, such as Fe and Ti. Summary of the invention
[0005] The first purpose of the present invention is to solve the technical problem that the above-mentioned prior art uses less endogenous characteristic elements (such as Fe and Ti) in solid wastes such as iron tailings. The present invention provides a microcrystalline cast stone and a preparation method thereof, which is mainly based on vanadium-titanium magnet tailings, and utilizes endogenous characteristic elements such as Fe and Ti in the vanadium-titanium magnet tailings as nucleating agents in the production process of microcrystalline cast stone to achieve a low addition amount of nucleating agent, and even when the content of TiO2 and / or Fe2O3 in the vanadium-titanium magnet tailings is high enough, zero addition of nucleating agent can be achieved.
[0006] The first aspect of the present invention provides a method for preparing microcrystalline cast stone, wherein the raw materials used contain 35%-70wt% of vanadium-titanium magnet tailings; wherein the TiO2 content in the vanadium-titanium magnet tailings is not less than 0.9wt%, and / or the Fe2O3 content is not less than 9.8wt%, and / or the raw materials also include not more than 7wt% of a nucleating agent.
[0007] The present invention uses vanadium-titanium magnet tailings as the main raw material, and utilizes the endowment characteristic elements such as Fe and Ti in the vanadium-titanium magnet tailings as nucleating agents in the production process of microcrystalline cast stone, so as to achieve a low addition amount of nucleating agent, and even when the content of TiO2 and / or Fe2O3 in the vanadium-titanium magnet tailings is high enough, zero addition of nucleating agent can be achieved.
[0008] Preferably, the raw materials include 35%-55wt% of vanadium-titanium magnetite tailings and 35-55wt% of iron tailings. Using vanadium-titanium magnetite tailings and iron tailings as the main raw materials and supplemented with other solid waste raw materials to prepare microcrystalline cast stone can achieve nearly all solid waste preparation of microcrystalline cast stone, without the need to add additional aluminum and magnesium chemicals, thereby reducing costs.
[0009] Preferably, the raw material also includes 0-8wt% of high-aluminum solid waste and 0-5wt% of high-magnesium solid waste, the contents of the high-aluminum solid waste and high-magnesium solid waste are not 0 at the same time, and preferably the total amount of the two is not less than 3wt%. Among them, the content of Al2O3 in the high-aluminum solid waste is not less than 30wt%, and the content of MgO in the high-magnesium solid waste is not less than 10wt%. By reasonably matching high-aluminum solid waste, high-magnesium solid waste with vanadium-titanium magnet tailings and iron tailings, it is possible to achieve nearly all solid waste preparation of microcrystalline cast stone, and the solid waste rate in the raw material can reach more than 90%, and even more than 94%.
[0010] In some preferred embodiments of the present invention, the high-aluminum solid waste is selected from at least one of coal gangue, red mud, and aluminum slag.
[0011] In some preferred embodiments of the present invention, the high-magnesium solid waste is selected from at least one of slag, magnesium slag, and high-magnesium tailings.
[0012] Preferably, the raw material further comprises 0-7wt% of a nucleating agent and / or a crystallization aid; preferably, the mass ratio of the nucleating agent to the crystallization aid is 1:0.3~2. The present invention has experimentally found that when the nucleating agent and the crystallization aid are compounded in a specific ratio, the crystallization process is more favorable, the proportion of the crystalline phase is higher, the grain distribution is more uniform, etc.
[0013] In some preferred embodiments of the present invention, the nucleating agent is selected from at least one of iron oxide and titanium oxide.
[0014] In some preferred embodiments of the present invention, the crystallization aid is selected from at least one of zinc oxide and cerium oxide.
[0015] Preferably, the raw material formula is: 35-70 parts by weight of vanadium-titanium magnetite tailings, 18-55 parts of iron tailings, 0-8 parts of high-aluminum solid waste, 0-5 parts of high-magnesium solid waste, 0-5 parts of nucleating agent, and 0-2 parts of crystallization aid. Preferably, the total of the above raw materials is 100 parts.
[0016] More preferably, the formula of raw materials is 35-55 parts of vanadium-titanium magnetite tailings, 35-55 parts of iron tailings, 0-8 parts of high-aluminum solid waste, 0-5 parts of high-magnesium solid waste, 0-5 parts of nucleating agent, and 0-2 parts of crystallization aid, and the total of the above raw materials is preferably 100 parts.
[0017] Further preferably, the formula of raw materials is 40-45 parts of vanadium-titanium magnetite tailings, 40-45 parts of iron tailings, 4-8 parts of high-aluminum solid waste, 0-4 parts of high-magnesium solid waste, 2-4 parts of nucleating agent, and 1-2 parts of crystallization aid; preferably, the total of the above raw materials is 100 parts.
[0018] The present invention has been found through experiments that the microcrystalline stones obtained by using the raw materials in the above specific ratio have better mechanical properties, wear resistance and acid and alkali resistance.
[0019] The present invention uses vanadium-titanium magnet tailings as the main raw material, utilizes the endowment characteristic elements such as Fe and Ti in the vanadium-titanium magnet tailings as nucleating agents in the production process of microcrystalline cast stone, further, uses vanadium-titanium magnet tailings and iron tailings as the main raw materials, supplemented by other solid waste raw materials to prepare microcrystalline cast stone, rationally matches solid wastes, increases the solid waste dosage, and develops a method for preparing microcrystalline cast stone with vanadium-titanium magnet tailings as the main solid waste. The microcrystalline cast stone is synthesized by a one-step method, the process is simple, and no additional aluminum and magnesium chemicals need to be added, thereby reducing costs.
[0020] In the present invention, solid waste raw materials such as iron tailings and vanadium-titanium magnetite tailings need to be tested for composition in advance, the raw material particle size is not greater than 150 μm, and the batching process needs to be mixed evenly. The advantage of this is that the raw materials can be completely melted at a lower melting temperature and a faster melting rate, thereby improving efficiency, extending the service life of the equipment, and ensuring safe operation.
[0021] In some preferred embodiments of the present invention, the main components of the vanadium-titanium magnetite tailings are: SiO2: 44.4%, CaO: 21.4%, MgO: 11.6%, Fe2O3: 9.8%, Al2O3: 8.3%, and TiO2: 0.9%.
[0022] In other embodiments of the present invention, the main components of the vanadium-titanium magnetite tailings are: SiO2: 48.4%, CaO: 16.8%, MgO: 11.6%, Fe2O3: 9.8%, Al2O3: 8.3%, and TiO2: 0.9%.
[0023] The above vanadium-titanium magnetite tailings have a TiO2 content sufficient to serve as a nucleating agent in the crystallization process, so there is no need to add additional chemical nucleating agents such as TiO2.
[0024] In some preferred embodiments of the present invention, the main components of the iron tailings are: SiO2: 65.5%, CaO: 4.8%, MgO: 3.5%, Fe2O3: 9.9%, Al2O3: 8.6%, and TiO2: 0.4%.
[0025] In some preferred embodiments of the present invention, the main components of coal gangue are: SiO2: 44.6%, CaO: 0.5%, MgO: 0.2%, Fe2O3: 0.5%, Al2O3: 35.5%, and TiO2: 0.7%.
[0026] In some preferred embodiments of the present invention, the main components of the slag are: SiO2: 25.3%, CaO: 31.2%, MgO: 11.5%, Fe2O3: 1.84%, Al2O3: 13.4%, TiO2: 13.2%.
[0027] The use of the above-mentioned specific solid waste can provide the required Mg and Al without the need to add additional magnesium and aluminum chemicals, thereby achieving the effect of reducing costs and rationally utilizing resources.
[0028] The preparation method comprises the steps of melting the raw material at high temperature and then performing casting and crystallization treatment in sequence, wherein the temperature range of the high temperature melting is 1400-1500°C; And / or, during casting, the mold is a high temperature resistant metal mold, and preferably the mold temperature is maintained at 500-600°C during casting; And / or, the crystallization treatment is: heating from 500-600°C to 670-730°C, with a heating rate of 3-5°C and a holding time of 30-60min; heating from 670-730°C to 920-980°C, with a heating rate of 2-4°C and a holding time of 40-80min; heating from 920-980°C to 1050-1100°C, with a heating rate of 2-4°C and a holding time of 30-60min.
[0029] The present invention uses vanadium-titanium magnet tailings as the main raw material and adopts a specific heat treatment process to efficiently complete the crystallization process. The obtained microcrystalline cast stone has a high proportion of crystalline phase, uniform grain distribution, a grain size of 5-15μm, excellent mechanical properties, good wear resistance, and excellent acid and alkali resistance.
[0030] Furthermore, after the crystallization treatment is completed, furnace cooling is adopted during cooling, and the temperature in the furnace gradually decreases, so that the product yield is high and the defective product rate is low.
[0031] A second aspect of the present invention provides a microcrystalline cast stone, which is prepared by the above-mentioned method for preparing microcrystalline cast stone.
[0032] The third aspect of the present invention provides the application of the microcrystalline cast stone in the fields of architectural decoration, chemical industry, metallurgy, etc. Therefore, a building material can be obtained, comprising the microcrystalline cast stone.
[0033] The present invention uses vanadium-titanium magnet tailings as the main raw material, supplemented by other solid waste raw materials to prepare microcrystalline cast stone, and the preparation steps are batching and mixing, high-temperature melting, casting and molding, crystallization treatment, cooling, and cutting. The microcrystalline cast stone is synthesized by a one-step method, and the process is simple. The present invention uses endowment characteristic elements such as Fe and Ti in vanadium-titanium magnet tailings as nucleating agents in the production process of microcrystalline cast stone, and at the same time reasonably matches solid wastes to increase the solid waste dosage, and develops a method for preparing microcrystalline cast stone with vanadium-titanium magnet tailings as the main solid waste.
[0034] The microcrystalline cast stone product obtained by the present invention has excellent performance, good compressive strength and flexural strength, and also good acid and alkali resistance and wear resistance. Specifically, in some embodiments, the compressive strength can reach 860.8MPa, or even 908.29MPa; the bearing strength can reach 238MPa; the acid resistance (20% sulfuric acid solution, 1.84 g / cm 3 Sulfuric acid) can reach more than 99%; alkali resistance (20% NaOH) can reach more than 99%; wear resistance can reach 0.020 g / cm 2 . It has broad application prospects in the fields of building decoration, chemical industry, metallurgy, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0036] Figure 1A This is one of the scanning electron microscope (SEM) images of the microcrystalline cast stone provided by the present invention.
[0037] Figure 1B yes Figure 1A One of the enlarged partial views of the microcrystalline cast stone shown.
[0038] Figure 2 It is one of the X-ray diffraction patterns (XRD patterns) of the microcrystalline cast stone provided by the present invention.
[0039] Figure 3A This is the second scanning electron microscope (SEM) image of the microcrystalline cast stone provided by the present invention.
[0040] Figure 3B yes Figure 3A One of the enlarged partial views of the microcrystalline cast stone shown.
[0041] Figure 4 This is the second X-ray diffraction pattern (XRD pattern) of the microcrystalline cast stone provided by the present invention. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] In the following examples, the raw materials involved are all commercially available, among which chemicals such as iron oxide, zinc oxide, cerium oxide, titanium oxide, etc. are of analytical grade and purchased from Sinopharm Group Beijing Co., Ltd.
[0044] Example 1
[0045] A method for preparing microcrystalline cast stone from high-doped vanadium-titanium magnetite tailings, the preparation method is as follows: The preparation method comprises the following steps: (1) Raw material selection: the main raw materials are vanadium-titanium magnetite tailings, iron tailings, coal gangue, iron oxide, zinc oxide, and cerium oxide; (2) Chemical composition testing of raw materials: The main components of vanadium-titanium magnetite tailings are: SiO2: 44.4%, CaO: 21.4%, MgO: 11.6%, Fe2O3: 9.8%, Al2O3: 8.3%, TiO2: 0.9%; The main components of iron tailings: SiO2: 65.5%, CaO: 4.8%, MgO: 3.5%, Fe2O3: 9.9%, Al2O3: 8.6%, TiO2: 0.4%; The main components of coal gangue: SiO2: 44.6%, CaO: 0.5%, MgO: 0.2%, Fe2O3: 0.5%, Al2O3: 35.5%, TiO2: 0.7%.
[0046] The percentage of ingredients is 44% vanadium-titanium magnetite tailings, 42% iron tailings, 8% coal gangue, 4% iron oxide, 1% cerium oxide, and 1% zinc oxide.
[0047] The preparation process comprises the following steps: firstly sieving all raw materials to control the particle size of the raw materials to be no higher than 150 μm, then mixing the raw materials uniformly according to the above ingredients, adding the raw materials into a high-temperature furnace, melting the raw materials at 1450°C, and pouring the raw materials into a prepared heat-insulating mold after being completely melted, with the mold temperature at 580°C. After the pouring is completed, the product in the mold is subjected to a crystallization treatment, heating from 580°C to 680°C at a heating rate of 5°C / min, and keeping the temperature for 60 minutes for nucleation, heating from 680°C to 950°C at a heating rate of 3°C / min, and keeping the temperature for 60 minutes for crystallization, heating from 950°C to 1100°C at a heating rate of 3°C / min, and keeping the temperature for 30 minutes, cooling the raw materials with the furnace, trimming the raw materials after cooling out of the furnace, and then cutting the raw materials to obtain the microcrystalline cast stone.
[0048] The obtained products are subjected to performance testing, including SEM scanning, XRD analysis, and testing of compressive strength, flexural strength, acid resistance, alkali resistance and wear resistance, etc. The specific testing methods all adopt commonly used testing methods.
[0049] The electron scanning electron image (SEM image) and XRD image of the obtained microcrystalline cast stone are shown in Figures 1 and Figure 2 As shown in Figure 1, the surface of the obtained microcrystalline cast stone is relatively flat and dense, the grain size is evenly distributed, and most of the grains are about 10-15 microns in size. The formation of a large number of microcrystals can greatly improve the mechanical properties of the cast stone products on the one hand, and also have a good effect on improving the wear resistance of the products on the other hand. Figure 2 It can be concluded that the main components of the obtained microcrystalline cast stone are pyroxene and diopside, and the pyroxene phase has excellent acid and alkali resistance.
[0050] Judging from the microstructure, the prepared cast stone products should have good mechanical properties, wear resistance and resistance to acid and alkali corrosion. The test results of the product's compressive strength, flexural strength, acid resistance, alkali resistance and wear resistance are shown in Tables 1 and 2.
[0051] Table 1
[0052] Table 2
[0053] Example 2
[0054] A method for preparing microcrystalline cast stone from high-doped vanadium-titanium magnetite tailings, the preparation method is as follows: The preparation method comprises the following steps: (1) Raw material selection: the main raw materials are vanadium-titanium magnetite tailings, iron tailings, coal gangue, slag, iron oxide, zinc oxide, and cerium oxide; (2) Chemical composition testing of raw materials: The main components of vanadium-titanium magnetite tailings are: SiO2: 48.4%, CaO: 16.8%, MgO: 11.6%, Fe2O3: 9.8%, Al2O3: 8.3%, TiO2: 0.9%; The main components of iron tailings: SiO2: 65.5%, CaO: 4.8%, MgO: 3.5%, Fe2O3: 9.9%, Al2O3: 8.6%, TiO2: 0.4%; The main components of coal gangue: SiO2: 44.6%, CaO: 0.5%, MgO: 0.2%, Fe2O3: 0.5%, Al2O3: 35.5%, TiO2: 0.7%.
[0055] The main components of slag: SiO2: 25.3%, CaO: 31.2%, MgO: 11.5%, Fe2O3: 1.84%, Al2O3: 13.4%, TiO2: 13.2%.
[0056] The percentage of ingredients is 70% vanadium-titanium magnetite tailings, 18% iron tailings, 4% coal gangue, 4% slag, 2% iron oxide, 1% cerium oxide, and 1% zinc oxide.
[0057] In the preparation process, all the raw materials are first sieved to control the particle size of the raw materials to be no higher than 150μm, and then the above ingredients are mixed evenly, added to a high-temperature furnace, melted at 1450℃, and poured into a prepared insulation mold after complete melting. The mold temperature is 600℃. After pouring, the product in the mold is crystallized, heated from 600℃ to 700℃, with a heating rate of 5℃ / min, and kept warm for 60min for nucleation, heated from 700℃ to 950℃, with a heating rate of 3℃ / min, and kept warm for 60min for crystallization, heated from 950℃ to 1100℃, with a heating rate of 3℃ / min, and kept warm for 30min, cooled with the furnace, and then cut to obtain the product for performance testing.
[0058] The obtained products are subjected to performance testing, including SEM scanning, XRD analysis, and testing of compressive strength, flexural strength, acid resistance, alkali resistance and wear resistance, etc. The specific testing methods all adopt commonly used testing methods.
[0059] The electron scanning electron image (SEM image) and XRD image of the obtained microcrystalline cast stone are shown in Figures 3 and Figure 4 As shown in Figure 3, the obtained microcrystalline cast stone is dense inside without obvious pores, the grain size is evenly distributed, and most of the grains are about 5-15 microns in size. The formation of a large number of microcrystals greatly improves the mechanical properties of the cast stone products. In addition, it also has a good effect on improving the wear resistance of the product. Figure 4 It can be concluded that the main components of the obtained microcrystalline cast stone are pyroxene and diopside, and the pyroxene phase has excellent acid and alkali resistance.
[0060] The test results of compressive strength, flexural strength, acid resistance, alkali resistance and wear resistance are shown in Tables 3 and 4. It can be seen that the prepared cast stone products have excellent mechanical properties and resistance to acid and alkali erosion, which is consistent with the results of microstructural judgment.
[0061] Table 3
[0062] Table 4
[0063] A comprehensive analysis of the embodiments shows that microcrystalline cast stone products with excellent performance can be prepared by using high-doped vanadium-titanium magnet tailings in combination with other solid waste raw materials. From the microscopic structure, the product has a high proportion of crystalline phase, uniform grain distribution, and appropriate grain size; from a macroscopic point of view, the product exhibits excellent mechanical properties and acid and alkali resistance.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing microcrystalline cast stone, characterized in that: The raw materials used contain 35-70wt% vanadium-titanium magnetite tailings; Among them, the TiO2 content in the vanadium-titanium magnet tailings is not less than 0.9wt%, and / or the Fe2O3 content is not less than 9.8wt%, and / or the raw material also includes a nucleating agent of not more than 7wt%.
2. The method for preparing microcrystalline cast stone according to claim 1, characterized in that: The raw materials include 35-55wt% of vanadium-titanium magnetite tailings and 35-55wt% of iron tailings.
3. The method for preparing microcrystalline cast stone according to claim 2, characterized in that: The raw materials also include 0-8wt% of high-aluminum solid waste and / or 0-5wt% of high-magnesium solid waste, the contents of the high-aluminum solid waste and high-magnesium solid waste are not 0 at the same time, and preferably the total amount of the two is not less than 3wt%; Among them, the content of Al2O3 in the high-aluminum solid waste is not less than 30wt%, and the content of MgO in the high-magnesium solid waste is not less than 10wt%.
4. The method for preparing microcrystalline cast stone according to claim 3, characterized in that: The high-aluminum solid waste is selected from at least one of coal gangue, red mud, and aluminum slag; and / or, the high-magnesium solid waste is selected from at least one of slag, magnesium slag, and high-magnesium tailings.
5. The method for preparing microcrystalline cast stone according to claim 3, characterized in that: The raw material also includes 0-7wt% of a nucleating agent and / or a crystallization aid; preferably, the mass ratio of the nucleating agent to the crystallization aid is 1:0.3-2.
6. The method for preparing microcrystalline cast stone according to claim 5, characterized in that: The nucleating agent is selected from at least one of iron oxide and titanium oxide, and / or the crystallization aid is selected from at least one of zinc oxide and cerium oxide.
7. The method for preparing microcrystalline cast stone according to claim 1, characterized in that: In parts by weight, the raw material formula is: 35-70 parts of vanadium-titanium magnetite tailings, 18-55 parts of iron tailings, 0-8 parts of high-aluminum solid waste, 0-5 parts of high-magnesium solid waste, 0-5 parts of nucleating agent, and 0-2 parts of crystallization aid; Preferably, the formula of the raw materials is 35-55 parts by weight of vanadium-titanium magnetite tailings, 35-55 parts of iron tailings, 0-8 parts of high-aluminum solid waste, 0-5 parts of high-magnesium solid waste, 0-5 parts of nucleating agent, and 0-2 parts of crystallization aid; More preferably, the formula of raw materials is 40-45wt% of vanadium-titanium magnetite tailings, 40-45wt% of iron tailings, 4-8wt% of high-aluminum solid waste, 0-4wt% of high-magnesium solid waste, 2-4wt% of nucleating agent, and 1-2wt% of crystallization aid.
8. The method for preparing microcrystalline cast stone according to any one of claims 1 to 7, comprising the steps of melting the raw material at high temperature and then performing casting and crystallization treatment in sequence, wherein: The temperature range of the high temperature melting is 1400-1500°C; And / or, during the casting process, the mold temperature is maintained at 500-600°C; And / or, the crystallization treatment is: heating from 500-600°C to 670-730°C, with a heating rate of 3-5°C and a holding time of 30-60min; heating from 670-730°C to 920-980°C, with a heating rate of 2-4°C and a holding time of 40-80min; heating from 920-980°C to 1050-1100°C, with a heating rate of 2-4°C and a holding time of 30-60min.
9. A microcrystalline cast stone, characterized in that: The preparation method is described in any one of claims 1 to 8.
10. A building material, characterized in that: Including the microcrystalline cast stone as described in claim 9.
Citation Information
Cited By
Method for preparing black microlite from titanium-containing blast furnace slag
CN121020992A
Method for preparing porous microlite by melting titanium-containing blast furnace slag
CN121021016A
A method for preparing porous microcrystalline stone from molten titanium-containing blast furnace slag
CN121021016B